Spinel type ferrite with ferromagnetic property, preparation method and application thereof, and wave-absorbing material
By plating, quenching, cooling and heat treatment of metal oxides, spinel-type ferrite with ferromagnetic properties is prepared, which solves the shortcomings of existing materials in wave absorption performance, and achieves lower reflection loss and wide effective bandwidth.
Patent Information
- Application Number
- CN202411638986.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-25
AI Technical Summary
The existing spinel type ferrite materials have a high minimum reflection loss during the preparation process and a narrow effective bandwidth, which makes it difficult to achieve good wave absorption performance in practical applications.
Spinel type ferrite with ferromagnetic properties is prepared by sequentially tableting, quenching, cooling and heat treatment of metal oxides (such as FeO, NiO, CoO). The method includes quenching treatment within the range of 1400 to 1600°C and heat treatment under a protective atmosphere to reduce the minimum reflection loss and expand the effective bandwidth.
The prepared spinel-type ferrite exhibits strong wave absorption performance at a thickness of 1 to 5 mm, with a minimum reflection loss of less than -10dB, an effective bandwidth of more than 2.8GHz, and its performance is much higher than that of materials prepared by soft chemical method.
Smart Images

Figure CN119683985A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ferrites, and in particular to a spinel ferrite with ferromagnetic properties, a preparation method and application thereof, and a wave absorbing material. Background Art
[0002] Spinel ferrite is a wave-absorbing material with excellent magnetic properties. Due to its high Curie temperature and coercivity, it can show strong magnetism and high saturation magnetization at room temperature, so it is widely used in electromagnetic equipment, sensors, electromagnetic wave absorption and other fields. Cubic spinel ferrite materials have the advantages of low saturation magnetic moment, superparamagnetism, high magnetic susceptibility, etc., and are good soft magnetic materials.
[0003] At present, most of the preparation methods of spinel ferrite are soft chemical methods such as sol-gel method, hydrothermal method, hydrolysis method, co-precipitation method, and dissolved salt method. The minimum reflection loss of the obtained spinel ferrite is high and the effective bandwidth is narrow. Therefore, it is difficult to achieve good absorbing performance in practical applications. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a spinel ferrite with ferromagnetic properties, a preparation method and application thereof, and a wave absorbing material. The spinel ferrite provided by the present invention has a small minimum reflection loss, a large effective bandwidth, and excellent wave absorbing performance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a method for preparing spinel ferrite with ferromagnetic properties, comprising the following steps: sequentially tabletting, quenching, cooling and heat treating metal oxide to obtain spinel ferrite with ferromagnetic properties; the metal oxide comprises FeO; the quenching temperature is 1400-1600°C; and the heat treatment is performed under a protective atmosphere.
[0007] Preferably, the metal oxide further comprises NiO and / or CoO;
[0008] The particle size of the metal oxide is <100 nm.
[0009] Preferably, the mass of NiO accounts for less than 30wt% of the total mass of FeO and NiO;
[0010] The mass of the CoO is less than 30 wt % of the total mass of FeO and CoO.
[0011] Preferably, when the metal oxide further includes NiO and / or CoO, the metal oxide is firstly ball-milled and mixed, and the obtained metal oxide ball-milled powder is then tableted;
[0012] The particle size of the metal oxide ball-milled powder is less than 100 nm.
[0013] Preferably, the heat treatment temperature is 500-750° C., and the holding time is 1-5 hours; the heating rate from room temperature to the heat treatment temperature is 1-10° C. / min.
[0014] Preferably, the quenching holding time is 0.5 to 5 hours; the heating rate from room temperature to the quenching temperature is 1 to 10° C. / min.
[0015] Preferably, the cooling comprises water cooling.
[0016] Preferably, after the water cooling, the method further comprises: drying, grinding and sieving the water-cooled sample in sequence.
[0017] The present invention also provides spinel ferrite with ferromagnetic properties obtained by the preparation method described in the above technical solution.
[0018] The present invention also provides the use of the spinel ferrite with ferromagnetic properties described in the above technical solution in wave absorbing materials.
[0019] The present invention also provides a wave absorbing material, comprising the spinel ferrite with ferromagnetic properties and a dielectric material as described in the above technical solution.
[0020] The present invention provides a method for preparing spinel ferrite with ferromagnetic properties, comprising the following steps: pressing, quenching, cooling and heat treating metal oxides in sequence to obtain spinel ferrite with ferromagnetic properties; the metal oxides include FeO; the quenching temperature is 1400-1600°C; the heat treatment is carried out under a protective atmosphere. The spinel ferrite with ferromagnetic properties prepared by the present invention exhibits strong wave absorption performance at a thickness of 1-5 mm, and the minimum reflection loss has a reflection loss of less than -10 dB in different bands, and the minimum reflection loss is small. The effective bandwidth of the prepared spinel ferrite with ferromagnetic properties is also basically more than 2.8 GHz, the effective bandwidth is large, and the performance is much better than the spinel ferrite prepared by the soft chemical method. It can be compounded with other dielectric materials to show stronger wave absorption performance, and the minimum reflection loss and effective absorption bandwidth will also be greatly improved according to the performance of the dielectric composite material; the spinel ferrite with ferromagnetic properties prepared by the present invention has a high saturation magnetization intensity and meets the use requirements. Furthermore, the preparation method provided by the present invention has simple process, simple operation, low cost and is suitable for industrial production.
[0021] Furthermore, the present invention can achieve regulation of the wave absorption frequency band and magnetic properties of the spinel ferrite with ferromagnetic properties by controlling the addition amounts of NiO and CoO in the spinel ferrite with ferromagnetic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the binary phase diagram of FeO-NiO;
[0023] Figure 2 It is the binary phase diagram of FeO-CoO;
[0024] Figure 3 XRD spectra of spinel ferrite (quenching temperature is 1600℃) with different NiO addition amounts;
[0025] Figure 4 XRD spectra of spinel ferrite (quenching temperature is 1600℃) with different CoO addition amounts;
[0026] Figure 5 Generate reflection loss plots of different thicknesses of spinel ferrite with ferromagnetic properties for FeO;
[0027] Figure 6 3D graph (left) and projection graph (right) of reflection loss of spinel nickel ferrite with ferromagnetic properties at different thicknesses with different NiO addition amounts;
[0028] Figure 7 3D graph (left) and projection graph (right) of reflection loss of spinel nickel ferrite with ferromagnetic properties at different thicknesses with different NiO addition amounts;
[0029] Figure 8 3D graph (left) and projection graph (right) of reflection loss of spinel nickel ferrite with ferromagnetic properties at different thicknesses with different NiO addition amounts;
[0030] Figure 6 to Figure 8 Among them, a and b are added in an amount of 0%, c and d are added in an amount of 5%, e and f are added in an amount of 10%, g and h are added in an amount of 15%, i and j are added in an amount of 20%, k and l are added in an amount of 25%, and m and n are added in an amount of 30%;
[0031] Fig. 9 3D graph (left) and projection graph (right) of reflection loss of spinel cobalt ferrite with ferromagnetic properties at different thicknesses with different CoO addition amounts;
[0032] Fig.10 3D graph (left) and projection graph (right) of reflection loss of spinel cobalt ferrite with ferromagnetic properties at different thicknesses with different CoO addition amounts;
[0033] Fig. 9 and Fig.10 Among them, a and b are added in an amount of 5%, c and d are added in an amount of 10%, e and f are added in an amount of 15%, g and h are added in an amount of 20%, i and j are added in an amount of 25%, and k and l are added in an amount of 30%. DETAILED DESCRIPTION
[0034] The invention provides a method for preparing spinel ferrite with ferromagnetic properties, comprising the following steps: sequentially tabletting, quenching, cooling and heat treating metal oxide to obtain spinel ferrite with ferromagnetic properties; the metal oxide comprises FeO; the quenching temperature is 1400-1600°C; and the heat treatment is performed under a protective atmosphere.
[0035] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0036] In the present invention, the metal oxide preferably further comprises NiO and / or CoO, more preferably NiO or CoO. In the present invention, the mass of the NiO preferably accounts for less than 30wt% of the total mass of FeO and NiO. In a specific embodiment, the mass of the NiO may account for 0wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt% of the total mass of FeO and NiO. The present invention can achieve the regulation of the absorption frequency band and magnetic properties of the spinel ferrite with ferromagnetic properties by controlling the amount of NiO added.
[0037] In the present invention, the mass of the CoO preferably accounts for less than 30wt% of the total mass of FeO and CoO. In a specific embodiment, the mass of the CoO may account for 0wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt% of the total mass of FeO and CoO. The present invention can achieve the regulation of the absorption frequency band and magnetic properties of the spinel ferrite with ferromagnetic properties by adding CoO.
[0038] In the present invention, the particle size of the metal oxide is preferably <100 nm, and the raw material has a small particle size and good dispersibility.
[0039] In the present invention, when the metal oxide also includes NiO and / or CoO, it is preferred to firstly ball-mill the metal oxide, and then press the obtained metal oxide ball-milled powder into tablets. In the present invention, the ball-milling mixing preferably includes wet ball milling, and the dispersion liquid used in the wet ball milling mixing preferably includes anhydrous ethanol; the rotation speed of the ball milling mixing is preferably 200-500 r / min, and in specific embodiments, it can be 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min or 500 r / min; the ball-to-material ratio of the ball milling mixing is preferably 2-20:1, and in specific embodiments, it can be 2:1, 5:1, 10:1, 15:1 or 20:1; The grinding balls used in the ball milling mixing preferably include large balls, medium balls and small balls. The particle size of the large balls is preferably 5-10 mm, the particle size of the medium balls is preferably 2-6 mm, and the particle size of the small balls is preferably 1-3 mm; the number ratio of the large balls, medium balls and small balls is preferably 1-4:4-6:10, and in specific embodiments it can be 1:4:10, 1:5:10, 1:6:10, 2:4:10, 2:5:10, 2:6:10, 3:4:10, 3:5:10, 3:6:10, 4:4:10, 4:5:10 or 4:6:10.
[0040] In the present invention, after the wet ball milling, the method preferably further comprises: washing the obtained grinding system and drying it to obtain a metal oxide ball milled powder; the washing agent used in the washing preferably comprises water and / or anhydrous ethanol; the drying temperature is preferably 20 to 60°C, and in a specific embodiment, it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C; the drying time is preferably 12 to 96 hours, and in a specific embodiment, it can be 12 hours. In the present invention, the particle size of the metal oxide ball milled powder is preferably <100nm.
[0041] The present invention has no particular limitation on the tableting, as long as the metal oxide can be in the form of sheets.
[0042] In the present invention, the quenching temperature is 1400-1600°C, and in specific embodiments it can be 1400°C, 1450°C, 1500°C, 1550°C or 1600°C; the heating rate from room temperature to the quenching temperature is preferably 1-10°C / min, and in specific embodiments it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min; the holding time of the quenching is preferably 0.5-5h, and in specific embodiments it can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h.
[0043] In the present invention, the quenching temperature is preferably determined by calculating the amount of NiO and / or CoO added using FactSage 8.3 software for material thermodynamics, so as to ensure that the substance generated by quenching the metal oxide is spinel ferrite. Figure 1 It is a binary phase diagram of FeO-NiO. It can be seen that when the mass ratio of NiO / (NiO+FeO) is 0-33% and the quenching temperature is between 1400 and 1600°C, nickel ferrite (NiFe2O4) with a spinel structure can be obtained. Figure 2 It is a binary phase diagram of FeO-CoO. It can be seen that when the mass ratio of CoO / (CoO+FeO) is 0-33% and the quenching temperature is 1400-1500°C, cobalt ferrite (CoFe2O4) with a spinel structure can be obtained.
[0044] According to the preparation method provided by the invention, the addition amount of NiO and CoO is 0-30wt%, and the quenching is carried out at a temperature of 1400-1600°C, and spinel ferrite with ferromagnetic properties can be generated.
[0045] In the present invention, the cooling preferably includes water cooling. In the present invention, the water cooling preferably further includes: drying, grinding and sieving the water-cooled sample in sequence. In the present invention, the drying temperature is preferably 20 to 60°C, and in specific embodiments it can be 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C. In the present invention, the particle size after grinding is preferably <75μm. In the present invention, the sieve size of the sieve is 200 mesh, and the part under the sieve is used.
[0046] In the present invention, the temperature of the heat treatment is preferably 500-750°C, and in a specific embodiment, it can be 500°C, 550°C, 600°C, 650°C, 700°C or 750°C; the heating rate from room temperature to the temperature of the heat treatment is preferably 1-10°C / min, and in a specific embodiment, it can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min; the holding time of the heat treatment is preferably 1-5h, and in a specific embodiment, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h; the heat treatment is carried out under a protective atmosphere, and the protective atmosphere includes nitrogen, argon or helium. In the present invention, the purpose of the heat treatment is to eliminate stress.
[0047] After completing the heat treatment, the present invention preferably further comprises cooling the heat-treated sample to room temperature to obtain spinel ferrite. In the present invention, the cooling rate is preferably 1 to 10°C / min, and in specific embodiments can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min.
[0048] The present invention also provides a spinel ferrite with ferromagnetic properties obtained by the preparation method described in the above technical solution. In the present invention, the thickness of the spinel ferrite with ferromagnetic properties is preferably 1 to 5 mm, and in specific embodiments, it can be 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm.
[0049] The spinel ferrite with ferromagnetic properties prepared by the present invention exhibits strong wave absorption performance at a thickness of 1 to 5 mm, and the minimum reflection loss is less than -10 dB in different bands. The effective bandwidth of the prepared spinel ferrite with ferromagnetic properties is basically more than 2.8 GHz, and the performance is much better than the spinel ferrite prepared by the soft chemical method. It can show stronger wave absorption performance by compounding it with other dielectric materials, and the minimum reflection loss and effective absorption bandwidth will also be greatly improved according to the performance of the dielectric composite material; the spinel ferrite with ferromagnetic properties prepared by the present invention has a high saturation magnetization intensity, which meets the use requirements. Furthermore, the present invention can achieve the regulation of the wave absorption frequency band and magnetic properties of the spinel ferrite with ferromagnetic properties by controlling the addition amount of NiO and CoO.
[0050] The present invention also provides the use of the spinel ferrite with ferromagnetic properties described in the above technical solution in wave absorbing materials.
[0051] The present invention also provides a wave absorbing material, comprising the spinel ferrite with ferromagnetic properties and a dielectric material as described in the above technical solution.
[0052] The present invention has no special limitation on the dielectric material, and any dielectric material well known to those skilled in the art may be used.
[0053] In the present invention, the content of spinel ferrite with ferromagnetic properties in the absorbing material is preferably 70-100wt%, and in specific embodiments it can be 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt% or 100wt%. When the content of spinel ferrite with ferromagnetic properties is 100wt%, no dielectric material is added.
[0054] To further illustrate the present invention, the spinel ferrite with ferromagnetic properties, its preparation method and application, and the wave absorbing material provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0055] The purity of the following metal oxide raw material powders is analytical grade.
[0056] Example 1
[0057] The pure FeO powder is pressed into a circular green body with a diameter of 35 mm, and placed in a corundum crucible; it is hung into the temperature sensing center of a high-temperature quenching furnace by using a molybdenum wire, and alumina furnace plugs are used above and below, and the temperature is raised to 1600°C at a rate of 5°C / min through induction heating, and the temperature is kept and quenched for 120 minutes. When the temperature is about to end, the quenching furnace is opened, and the sample is quenched in water to cool rapidly; the spinel ferrite sample in the water is collected, and placed in a drying oven at 30°C for 2 hours; it is ground to a particle size of less than 75μm, sieved through a 200-mesh sample sieve, and the sieved part is placed in a corundum crucible, which is placed in a tubular furnace, and argon is used as a protective gas. The temperature is raised to 700°C at a rate of 5°C / min, and the temperature is kept for heat treatment for 2 hours, and then the temperature is cooled to room temperature at a rate of 5°C / min to obtain a spinel ferrite with ferromagnetic properties.
[0058] Example 2
[0059] NiO was added to pure FeO powder, and the powder was put into a ball mill, with anhydrous ethanol as the dispersion liquid, the rotation speed was 300 r / min, the ball-to-material ratio was 10:1, the ratio of large, medium and small balls was 2:5:10, and the ball milling was performed for 6 hours to obtain a FeO+NiO mixture with a particle size of less than 100 nm (the mass of NiO accounted for 5% of the total mass of FeO and NiO, and the NiO addition amount was recorded as 5%). After washing and precipitation, the mixture was placed in a drying oven for 12 hours, taken out, pressed into a round green body with a diameter of 35 mm, put into a corundum crucible, and hung into the temperature sensing center of a high-temperature quenching furnace using a molybdenum wire. Alumina furnace plugs were used for insulation at the top and bottom, and the mixture was heated by induction at 5°C. The temperature is raised to 1600°C at a rate of 5°C / min, and the sample is quenched in water for 120 minutes. When the insulation is about to end, the quenching furnace is opened, and the sample is quenched in water to cool rapidly. The quenched sample in the water is collected and placed in a drying oven at 30°C for 2 hours. The sample is ground to a particle size of less than 75 μm, and the sample is sieved through a 200-mesh sample sieve. The portion under the sieve is placed in a corundum crucible, which is placed in a tubular furnace with argon as a protective gas. The temperature is raised to 700°C at a rate of 5°C / min, and the sample is heat treated by insulation for 2 hours. The sample is then cooled to room temperature at a rate of 5°C / min to obtain a spinel ferrite (denoted as 5%-NiO, which belongs to spinel nickel ferrite) having ferromagnetic properties.
[0060] Embodiments 3 to 7
[0061] According to the method of Example 2, spinel ferrite with ferromagnetic properties was prepared. The only difference between Examples 3 to 8 and Example 5 is that the amount of NiO added is 10%, 15%, 20%, 25% and 30% respectively. The obtained spinel ferrite with ferromagnetic properties is recorded as 10%-NiO, 15%-NiO, 20%-NiO, 25%-NiO and 30%-NiO respectively.
[0062] Figure 3 The XRD spectra of spinel ferrites with ferromagnetic properties prepared in Examples 1 to 7 with different NiO addition amounts show that the phases generated by high temperature quenching are all spinel ferrites, and with the increase of NiO addition amount, the diffraction peak of the product shifts from Fe3O4 (PDF#19-0629) to NiFe2O4 (PDF#54-0964) peak. This shows that NiFe2O4 can be successfully prepared by this method with NiO addition amount between 0 and 30% (and not 0). When NiO is not added, the product is mainly Fe3O4.
[0063] Embodiments 8 to 13
[0064] Spinel ferrite with ferromagnetic properties is prepared according to the method of Example 2. The only difference between Examples 8 to 13 and Example 2 is that NiO is replaced by CoO, and the amount of CoO added is 5%, 10%, 15%, 20%, 25% and 30% respectively. The obtained spinel ferrite with ferromagnetic properties (belonging to spinel cobalt ferrite) is recorded as 5%-CoO, 10%-CoO, 15%-CoO, 20%-CoO, 25%-CoO and 30%-CoO respectively.
[0065] Figure 4 The XRD spectra of spinel ferrites with ferromagnetic properties prepared in Examples 1 and 8 to 13 with different CoO addition amounts show that the phases generated by high temperature quenching are all spinel ferrites, and as the amount of CoO added increases, the diffraction peak of the product shifts from Fe3O4 (PDF#19-0629) to the right first, and then to the left CoFe2O4 (PDF#54-0964) peak. This shows that the method provided by the present invention can successfully prepare CoFe2O4 when the amount of CoO added is between 0 and 30% (and not 0). When CoO is not added, the product is mainly Fe3O4.
[0066] Table 1 shows the hysteresis loop data of spinel ferrite with ferromagnetic properties with different contents of NiO or CoO added.
[0067]
[0068]
[0069] It can be seen from Table 1 that when NiO is not added, the saturation magnetization (Ms) of Fe3O4 is 67.77emu / g, and the coercive force (Hc) is 16.537Oe. As the amount of NiO added increases, the saturation magnetization (Ms) of the spinel ferrite with ferromagnetic properties shows a trend of gradually decreasing first, and the saturation magnetization is the largest when the addition amount is 10%, which is 73.75emu / g. The coercive force of the spinel ferrite with ferromagnetic properties is relatively small, all below 20Oe, and the minimum is 4.729Oe when the addition amount is 25%. The reason may be that Ni 2+ Replace part of Fe 2+ , reducing the A-site atomic defects and enhancing the saturation magnetization, but with the increase of atomic replacement, new defects are generated, resulting in a decrease in the saturation magnetization.
[0070] With the increase of CoO addition, the saturation magnetization (Ms) of spinel ferrite with ferromagnetic properties shows a trend of gradually increasing first and then decreasing. The growth trend of coercive force is the same as the change trend of saturation magnetization, both of which show the maximum value of 81.03emu / g and 217.68Oe respectively when the addition amount is 25%.
[0071] Figure 5 The reflection loss diagram of different thicknesses of the spinel ferrite with ferromagnetic properties prepared in Example 1 shows that different thicknesses of spinel ferrite correspond to different absorbing frequency bands. At 2.5 mm, the main loss is in the X band, and the loss range is 7.84 to 11.44 GHz. The lowest reflection loss of -21.80 dB occurs at a thickness of 4.5 mm and 17.12 GHz.
[0072] Figure 6 to Figure 8 The reflection loss 3D diagram (left) and projection diagram (right) of different thicknesses of spinel ferrite with ferromagnetic properties with different NiO additions prepared in Example 1, where a and b additions are 0%, c and d additions are 5%, e and f additions are 10%, g and h additions are 15%, i and j additions are 20%, k and l additions are 25%, and m and n additions are 30%. It can be seen that different thicknesses correspond to different absorbing frequency bands and have different minimum reflection loss values. According to the effective bandwidth and minimum reflection loss, NiO additions of 0 to 30% all have certain absorbing properties, which are in line with the actual application values of absorbing materials. After analysis, NiO additions between 10 and 15% have excellent absorbing properties.
[0073] Figure 9-10 The 3D graph (left) and projection graph (right) of the reflection loss of spinel ferrite with ferromagnetic properties at different thicknesses with different CoO additions, among which a and b are added 5%, c and d are added 10%, e and f are added 15%, g and h are added 20%, i and j are added 25%, and k and l are added 30%. It can be seen that different thicknesses correspond to different absorbing frequency bands and have different minimum reflection loss values. According to the effective bandwidth and minimum reflection loss, the CoO addition of 0-30% has certain absorbing performance, which is in line with the actual application value of absorbing materials. After analysis, the absorbing performance is excellent when the CoO addition is 15%.
[0074] Comparison of seven groups of absorption data with NiO addition of 0%, 5%, 10%, 15%, 20%, 25% and 30% shows that the results are consistent with the phase diagram results. The products are all spinel-type, and the absorption performance increases first and then decreases. Between 10 and 15%, the absorption and energy absorption have the best value. Comparison of six groups of absorption data with CoO addition of 5%, 10%, 15%, 20%, 25% and 30% shows that when the addition amount is 15%, the spinel ferrite with ferromagnetic properties has the best absorption performance.
[0075] Comparative Example 1
[0076] The pure FeO powder is pressed into a round green body with a diameter of 35 mm and placed in a corundum crucible; it is suspended into the temperature sensing center of the high-temperature quenching furnace using molybdenum wire, and alumina furnace plugs are used for insulation above and below. Through induction heating, the temperature is raised to 1300°C at a rate of 5°C / min, and the insulation quenching is performed for 120 minutes. When the insulation is about to end, the quenching furnace is opened, and the sample is quenched in water to cool rapidly; the spinel ferrite sample in the water is collected, placed in a drying oven at 30°C and dried for 2 hours to obtain spinel ferrite. The color of the spinel ferrite prepared in this comparative example is not pure black, and some of it is light red, indicating that the sample phase has not completely changed. Combining the binary phase diagram and the XRD diagram, it can be found that the sample contains not only the spinel ferrite Fe3O4 diffraction peak, but also the Fe2O3 diffraction peak.
[0077] Comparative Example 2
[0078] The pure FeO powder is pressed into a round green body with a diameter of 35 mm and placed in a corundum crucible; it is suspended into the temperature sensing center of the high-temperature quenching furnace using molybdenum wire, and alumina furnace plugs are used for insulation above and below. Through induction heating, the temperature is raised to 1400°C at a rate of 5°C / min, and the insulation quenching is performed for 10 minutes. When the insulation is about to end, the quenching furnace is opened, and the sample is quenched in water to cool rapidly; the spinel ferrite sample in the water is collected, placed in a drying oven at 30°C and dried for 2 hours to obtain spinel ferrite. The color of the spinel ferrite prepared in this comparative example is not pure black, and some are light red, indicating that the sample phase has not completely changed. Combining the binary phase diagram and the XRD diagram, it can be found that the sample contains not only the spinel ferrite Fe3O4 diffraction peak, but also the Fe2O3 diffraction peak.
[0079] Comparative Example 3
[0080] The spinel ferrite was prepared according to the method of Example 1, and the only difference from Example 1 was that the heat treatment atmosphere was air. The color of the spinel ferrite prepared in this comparative example was not pure black, and some of them were light red, indicating that the sample phase had not been completely changed. Combining the binary phase diagram and the XRD diagram, it can be found that the sample not only contained the spinel ferrite Fe3O4 diffraction peak, but also the Fe2O3 diffraction peak, indicating that Fe3O4 was easily affected by temperature, and the internal stress of the material must be eliminated at high temperature under a protective atmosphere.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing spinel ferrite having ferromagnetic properties, characterized in that: The following steps are involved: The metal oxide is pressed into sheets, quenched, cooled and heat-treated in sequence to obtain spinel ferrite having ferromagnetic properties; The metal oxide includes FeO; The quenching temperature is 1400-1600°C; The heat treatment is carried out under a protective atmosphere.
2. The preparation method according to claim 1, characterized in that: The metal oxide further comprises NiO and / or CoO; The particle size of the metal oxide is <100 nm.
3. The preparation method according to claim 2, characterized in that: The mass of the NiO accounts for less than 30wt% of the total mass of FeO and NiO; The mass of the CoO is less than 30 wt % of the total mass of FeO and CoO.
4. The preparation method according to claim 2 or 3, characterized in that: When the metal oxide also includes NiO and / or CoO, the metal oxide is firstly ball-milled and mixed, and the obtained metal oxide ball-milled powder is then tableted; The particle size of the metal oxide ball-milled powder is less than 100 nm.
5. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment is 500-750° C., and the heat preservation time is 1-5 hours; the heating rate from room temperature to the temperature of the heat treatment is 1-10° C. / min.
6. The preparation method according to claim 1, characterized in that: The quenching holding time is 0.5 to 5 hours; the heating rate from room temperature to the quenching temperature is 1 to 10°C / min.
7. The preparation method according to claim 1, characterized in that: The cooling includes water cooling; After the water cooling, the method further comprises: drying, grinding and sieving the water cooled sample in sequence.
8. The spinel ferrite having ferromagnetic properties obtained by the preparation method according to any one of claims 1 to 7.
9. Use of the spinel ferrite with ferromagnetic properties as claimed in claim 8 in wave absorbing materials.
10. A wave absorbing material comprising the spinel ferrite with ferromagnetic properties as claimed in claim 8 and a dielectric material.